2014
DOI: 10.1021/jp509016c
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Behavior of Rod–Coil–Rod Triblock Copolymers in a Coil-Selective Solvent

Abstract: Recent experiments have reported that the self-assembly of conjugated polymers mimicking rod-coil-rod triblock copolymers (BCPs) in selective solvents exhibits unique aggregate morphologies. However, the nature of the arrangement of the polymers within the aggregates and the spatial organization of the aggregates remain an unresolved issue. We report the results of coarse-grained Langevin dynamics simulations, which investigated the self-assembly behavior of rod-coil-rod BCPs in a coil-selective solvent. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Otherwise, the diffusion time measured in the FCS experiment would be the same (or even faster as the hydrodynamic radius of the collapsed triblock would be smaller). Furthermore, our recent coarse-grained simulation did reveal the formation of cylindrical-shaped triblock aggregates 23 . Collectively, our data clearly reveals that the film-like spectral features observed for the triblock in toluene/poor solvent mixtures arises from aggregates comprising several triblock molecules rather than collapsed individual triblock chains with two P3HT ends packed together.…”
Section: Resultsmentioning
confidence: 75%
“…Otherwise, the diffusion time measured in the FCS experiment would be the same (or even faster as the hydrodynamic radius of the collapsed triblock would be smaller). Furthermore, our recent coarse-grained simulation did reveal the formation of cylindrical-shaped triblock aggregates 23 . Collectively, our data clearly reveals that the film-like spectral features observed for the triblock in toluene/poor solvent mixtures arises from aggregates comprising several triblock molecules rather than collapsed individual triblock chains with two P3HT ends packed together.…”
Section: Resultsmentioning
confidence: 75%
“…Self-assembly of charged polymers is a phenomenon of general interest. ,,, Aggregation is often observed in biological systems , and highly charged polyelectrolytes. , Examples include fibrillar proteins , (F-actin) and DNA strands. , In these systems, self-charge attraction due to condensation of multivalent counterions is considered as the driving force of aggregation. Atomistic and coarse-grained MD simulations have been used to study self-assembly in solutions of peptide amphiphiles, polyelectrolyte brushes, , and protein-like polymers as well as preformed bundles of “hairy-rod” polyelectrolytes such as poly­( p -phenylene) (PPP). ,, …”
Section: Introductionmentioning
confidence: 99%
“…Simulation predictions helped to rationalize the experimental findings. In a different study, Omar et al 25 reported the aggregation behavior of rod–coil–rod triblocks in a coil-selective solvent; these authors used Lennard-Jones potentials to model the nonbonded interactions and used Langevin dynamics instead of DPD. Their block copolymers were composed of a relatively small number of beads, specifically, six beads made each block and the composition was fixed, polymer concentration was also varied in a small range.…”
Section: Introductionmentioning
confidence: 99%